Distribution of dialkylphosphate metabolites and 1- hydroxypyrene in parent-toddler pairs from agricultural communities and their impacts on toddler’s developmental performance - Boonsita Suwannakul; Ajchamon Thammachai; Noppharath Sangkarit; Surat Hongsibsong; Ratana Sapbamrer (Ecotoxicology and Environmental Safety)
The widespread presence of pesticides and polycyclic aromatic hydrocarbons (PAHs) in agricultural settings raises significant concerns about early-life exposure and its potential impact on toddler health and development. This cross-sectional study evaluated exposure to organophosphate and PAH metabolites among 154 parent-toddler pairs in northern Thailand, focusing on developmental outcomes. Urinary levels of dialkylphosphate (DAP) metabolites and 1-hydroxypyrene (1-OHP) were measured. Results showed that toddlers had significantly higher geometric mean levels of total DAP metabolites with a geometric mean of 24.38 µg/g creatinine compared to 17.25 µg/g creatinine in parents. A significant positive correlation was observed between the urinary levels of total dimethylphosphate (total DMP) and 1-OHP in both parents and toddlers (r = 0.290 for total DMP, r = 0.485 for 1-OHP), indicating shared environmental exposures. Proximity to farmland was a significant factor, with shorter distances associated with higher urinary total DMP and total DAP levels in toddlers (Beta = −19.8, 95 %CI = −37.3, −2.3 for total DMP, and Beta = −27.5, 95 % CI = −47.7, −7.4 for total DAP). Toddlers’ behavior, such as playing on farmland, was linked to significantly elevated urinary 1-OHP levels (Beta = 121.5, 95 % CI = 8.5, 234.5). Notably, an inverse association was found between DMP levels and receptive communication scores (Beta = −0.009, 95 % CI = −0.018, −0.001), suggesting potential adverse effects on neurodevelopment. These findings underscore the vulnerability of toddlers in agricultural communities to environmental contaminants and emphasize the need for targeted interventions to reduce exposure risks and promote safer agricultural practices. The study provides crucial insights for future research and policy development in environmental health.